Comparison of presumed cardiac and respiratory causes of out-of-hospital cardiac arrest. (August 2018) - Orban, Jean-Christophe; Truc, Mathieu; Kerever, Sébastien; Novain, Michaël; Cattet, Florian; Plattier, Rémi; Nefzaoui, Mohamed; Hyvernat, Hervé; Raguin, Olivier; Kaidomar, Michel; Mongardon, Nicolas; Ichai, Carole
Abstract: Aims of the study: Most interventional and observational studies include cardiac arrest from cardiac origin. However, an increasing proportion of cardiac arrest results from an extra-cardiac origin, mainly respiratory. The aim of our study was to compare the characteristics and outcome of cardiac arrest patients according to the presumed cardiac or respiratory causes. Methods: This retrospective multicenter observational study included out-of-hospital cardiac arrest patients from presumed cardiac and respiratory origin treated with therapeutic hypothermia. Demographic data (age, sex, initial rhythm as shockable or non-shockable, durations of no-flow and low-flow), clinical evolution in ICU, lactate and outcome (CPC scale at ICU discharge) were compared between patients according to the presumed cardiac or respiratory origin of the cardiac arrest. Results: Two hundred and fifty-one cardiac arrest patients were included, 156 from presumed cardiac origin (62%) and 95 from presumed respiratory origin (38%). Patients with presumed cardiac cause presented more frequently a shockable rhythm (68% vs. 5%, p < 0.001), received more defibrillations attempts (2 [1–5] vs. 0 [0-0], <0.001) and needed less adrenaline (3 mg [0–5] vs. 4 mg [2–7], p = 0.01). The arterial lactate concentration on admission was higher in patients with presumed respiratory causes (6.3 mmol/L [4.2–9.8] vs. 3.2 mmol/L [1.6–5.0], p < 0.001). The proportion of patients presenting a favorable outcome was higher in the population with presumed cardiac causes, compared to its respiratory counterpart (42% vs. 19%, p < 0.001). Conclusions: Compared to presumed cardiac origin, a worse outcome and a different mode of death are associated with the presumed respiratory origin, resulting from a greater insult preceding cardiac arrest. The presumed cause of cardiac arrest could be integrated in the multimodal prognostication process.